Russia and the European Convention (or Court) of Human Rights: The End? - Bowring, Bill (Revue québécoise de droit international / Quebec Journal of International Law / Revista quebequense de derecho internacional, 2020)
Russia has been a member of the Council of Europe (CoE) for 25 years, and of the European Convention on Human Rights (ECHR) for 22 years, which is in itself a remarkable achievement on both sides. This article asks the questions: how has this been this possible? And is the close and mostly positive relationship between Russia and the Council of Europe and the European Court of Human Rights (ECtHR) about to come to an end? In order to answer these questions, I first provide an overview of the USSR’s late acknowledgment of the need for compliance in its internal affairs with UN standards, and especially the contribution of Mikhail Gorbachev. I follow this with an account of Russia’s accession to the CoE and ratification of the ECHR under Boris Yeltsin, and a snapshot of the popularity for Russians of complaining to Strasbourg. Second, I turn to the very controversial rulings by the Constitutional Court of the Russian Federation (CCRF) and new legislation on the question of the CCRF ruling on the “impossibility” for Russia of implementing judgments of the ECtHR. Third, I analyse the controversial Yukos case. This was in fact the second and last until now such ruling on impossibility. Fourth, the Parliamentary Assembly of the Council of Europe imposed sanctions on Russia following the illegal annexation by Russian of Crimea. Russia seemed poised to leave or be expelled from the CoE. But in 2019 a controversial deal was done. Fifth, I ask whether President Putin’s 2020 amendments to the 1993 Constitution really pose a threat to Russia’s continuing relationship with the CoE and the ECHR.